The Influence of Influencer Marketing and Online Customer Reviews on Repurchase Intention of Finally Found You Skincare on TikTok Application in Palu City: The Mediating Role of Customer Trust - Eliyanti, Anggi; Ponirin; Mubaraq, Rahmat; Farid (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of influencer marketing and online customer reviews on the repurchase intention of Finally Found You skincare products on TikTok in Palu City, with customer trust as a mediating variable. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with data collected from 120 respondents. The results indicate that online customer reviews and customer trust positively and significantly affect repurchase intention, while influencer marketing has no significant direct effect. Influencer marketing and online customer reviews significantly influence customer trust. The findings highlight the importance of strengthening customer trust to enhance repurchase intention in social commerce. Keywords: Influencer Marketing, Online Customer Review, Customer Trust, Repurchase Intention, Social Commerce, TikTok Shop, Skincare Products, Consumer Behavior